Shape-controlled cobalt phosphide nanoparticles as volatile organic solvent sensor. Issue 22 (5th May 2016) - Pradhan, Bapi; Kumar, Gundam Sandeep; Dalui, Amit; Khan, Ali Hossain; Satpati, Biswarup; Ji, Qingmin; Shrestha, Lok Kumar; Ariga, Katsuhiko; Acharya, Somobrata
Abstract : Shape-controlled cobalt phosphide nanostructures have been synthesized using a one-pot reaction strategy for sensing volatile organic solvent molecules. Abstract : Here we demonstrate shape-controlled cobalt phosphide nanostructures through a one-pot synthetic approach in a single step with precise control over the size, shape and composition. We found that the ratio of the cobalt precursor, phosphorus sources, capping ligands, and annealing time play a key role in determining the morphology of the cobalt phosphide nanostructures. For instance, a zero-to-one-dimensional nanostructure transformation was observed with an increase in annealing time. The aspect ratio of one-dimensional nanorods could flexibly be tuned by a subtle balance of cobalt precursor, phosphorous source and capping ligands. Furthermore, a rod-to-hollow sphere transformation could be observed upon a decrease in the phosphorous source. Of these nanostructures, branched nanowires showed an excellent volatile organic solvent vapor sensing performance selective to benzene compared to the linear chain hydrocarbon hexane. A novel yet simple synthesis strategy with wide varieties of a controlled morphology of cobalt phosphide is expected to open up a new avenue to design other metal phosphide nanostructures, which would offer superior applications in the field of energy harvesting and sensing.